(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The paper addresses the crisis in the relationship between theatrical and educational epistemologies in the context of the new curriculum guidelines for teacher training in Brazil (CNE Resolutions 02/2015 and 02/2019). As a case study, it looks at the curriculum of the Theater Degree course at the Universidade Estadual do Sudoeste da Bahia (Brazil) and its initiatives designed to combine the pedagogical and propaedeutic dimensions of drama. Based on contemporary studies in theater pedagogy, it establishes links between artistic praxis, theatrical theories and theater-education in order to resolve possible controversies about the conveyance of artistic composition principles in the training of theater teachers.